2019
DOI: 10.1177/1039856219839468
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialty training pathways in intellectual and developmental disability psychiatry in Australia and New Zealand: current status and future opportunities

Abstract: Objectives: This study aimed to examine the training experiences of and determine capacity to train future Australian and New Zealand psychiatrists working in intellectual and developmental disability mental health. Methods: Australian and New Zealand psychiatrists with expertise or interest in intellectual and developmental disability mental health completed an online survey detailing their training pathway, support for subspecialty training and capacity to provide rotations in this area. Results: Psychiatris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, this data is essential to identifying avenues for enhancing workforce capacity and is thus detailed in Eagelson et al (2019). 5 Our findings indicate there is an established IDDMH workforce across Australia and New Zealand providing support in multiple settings. However, closer analysis indicates a relatively small number are providing the majority of services.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, this data is essential to identifying avenues for enhancing workforce capacity and is thus detailed in Eagelson et al (2019). 5 Our findings indicate there is an established IDDMH workforce across Australia and New Zealand providing support in multiple settings. However, closer analysis indicates a relatively small number are providing the majority of services.…”
Section: Discussionmentioning
confidence: 68%
“…However, this data is essential to identifying avenues for enhancing workforce capacity and is thus detailed in Eagelson et al (2019). 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of experience in working with individuals with intellectual disability on choice of future work has been demonstrated widely, including in other health services, for instance, in Australia. 14 It is concerning, therefore, to find that at least one-third of areas do not currently require core trainees to undertake a clinical placement in developmental psychiatry. At present, a review of the curricula is being undertaken by the Royal College of Psychiatrists; therefore, there is potential for this to change in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey of Australian general practitioners examining barriers and solutions to providing high-quality healthcare to people with ID found that over a third of respondents said that they were not confident treating people with ID [ 14 ]. Similarly, Australian consultant and trainee psychiatrists rated their training in ID mental health as inadequate and voiced a lack of confidence to meet the needs of people with ID [ 15 , 16 ]. While Victorian psychiatrists reported improvements in ID mental health training in the decade prior to 2004, they expressed that further improvements were required [ 17 ].…”
Section: Introductionmentioning
confidence: 99%